2011
DOI: 10.1007/s10529-011-0761-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatitis C virus replication by single and dual small interfering RNA using an HCV-infected cell model

Abstract: Dual siRNA against different regions of gene in hepatitis C virus (HCV) synergistically inhibited replication of HCV RNA. An HCV-infected cell model was established, and HCV RNA and core protein were detected by RT-PCR and Western blot, respectively. Four HCV-specific siRNAs (siCore, siNS3, siNS4B, siNS5B) were designed and transfected into HCV-infected Huh7.5.1 cells. The antiviral efficacies of the siRNAs were compared using real time PCR and agarose gel electrophoresis. HCV replication in infected cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…It has been shown that the blockage of multiple physiological events mediating malignancy and tumor cell survival, or blockage of a single critical path at multiple points to maximize inhibition of that path, is likely to result in greater-than-additive inhibition of tumor cell growth and viability (25). Similarly, in more recent studies, in vitro RNAi experiments conducted against hepatitis C virus using combinatorial treatment with two siRNAs elicited a significant increase in antiviral effects (26).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the blockage of multiple physiological events mediating malignancy and tumor cell survival, or blockage of a single critical path at multiple points to maximize inhibition of that path, is likely to result in greater-than-additive inhibition of tumor cell growth and viability (25). Similarly, in more recent studies, in vitro RNAi experiments conducted against hepatitis C virus using combinatorial treatment with two siRNAs elicited a significant increase in antiviral effects (26).…”
Section: Discussionmentioning
confidence: 99%
“…HCV, as a single plus RNA virus that replicates in the cytoplasm of liver cells, is sensitive to RNAi and might be an ideal target for this therapy. Destruction of HCV RNA could induce failure of HCV replication, indicating that the use of siRNA could be a novel regulatory approach for molecular therapeutics 14 15 16 17 . HCV is also prone to mutation and escape from single antivirals, so it also applies to siRNAs and it is generally accepted that combinatorial approaches, or targeting of host dependency factors, are required to prevent emergence of escape mutants.…”
mentioning
confidence: 99%
“…Jackson and colleagues suggested that using multiple siRNA duplexes to silence the target gene increased the likelihood of observing the desired phenotype and expression pattern [ 60 ]. This approach was validated by Xing et al, who demonstrated synergistic inhibitory effects on viral replication through the use of dual siRNAs directed against distinct regions of hepatitis C virus genes, achieving superior outcomes at lower doses compared to those achieved with single siRNA treatment [ 172 ]. In contrast, Haasnoot et al cautioned that excessive influx of multiple siRNAs may lead to increased off-target effects and toxicity by saturating RNAi pathways [ 173 ].…”
Section: Challenges Of Sirna Treatments For Viral Infectionsmentioning
confidence: 99%